1988
DOI: 10.1088/0953-4075/21/6/013
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in elastic scattering of polarised electrons by optically active molecules

Abstract: Elastic scattering of polarised electrons by optically active molecules is treated on the basis of such a simplified muffin-tin model that a molecule consists only of non-overlapping spheres with spin-orbit interaction incorporated. The scattering problem is solved with the approach presented in an earlier paper, and only the lowest-order partial spin-flip amplitudes are taken into account. Asymmetry in scattering phenomena is described by in-plane components of the function W ( 0 ) which is defined in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Resonance features have, indeed, been found in the transmission spectrum of camphor (Stephen et al 1988), though at energies smaller than the 5 eV used by Campbell and Farago. The possible enhancement of the asymmetry A by resonances in the total electron cross section has been emphasized in several theoretical papers (Walker 1982, Hayashi 1988, Fandreyer et al 1990, Gallup 1994.…”
Section: Temporary Negative-ion Statesmentioning
confidence: 99%
“…Resonance features have, indeed, been found in the transmission spectrum of camphor (Stephen et al 1988), though at energies smaller than the 5 eV used by Campbell and Farago. The possible enhancement of the asymmetry A by resonances in the total electron cross section has been emphasized in several theoretical papers (Walker 1982, Hayashi 1988, Fandreyer et al 1990, Gallup 1994.…”
Section: Temporary Negative-ion Statesmentioning
confidence: 99%
“…Kessler (1982) suggested that multiple intramolecular Mott scattering can lead to phenomena analogous to optical activity. Hayashi (1985Hayashi ( ,1988 followed up this idea and calculated the spin polarisation for initially unpolarised electrons, scattered from some model molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical estimates of such effects have been derived by Rich et al(1982). Hayashi (1985Hayashi ( , 1988 performed numerical calculations in the framework of multiple scattering theory and showed in particular that polarisation phenomena can be greatly enhanced if resonances are present.…”
Section: Introductionmentioning
confidence: 99%